2019
DOI: 10.1186/s12862-019-1344-0
|View full text |Cite
|
Sign up to set email alerts
|

Live fast, diversify non-adaptively: evolutionary diversification of exceptionally short-lived annual killifishes

Abstract: BackgroundAdaptive radiations are triggered by ecological opportunity – the access to novel niche domains with abundant available resources that facilitate the formation of new ecologically divergent species. Therefore, as new species saturate niche space, clades experience a diversity-dependent slowdown of diversification over time. At the other extreme of the radiation continuum, non-adaptively radiating lineages undergo diversification with minimal niche differentiation when ‘spatial opportunity’ (i.e. area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 105 publications
(132 reference statements)
0
15
0
Order By: Relevance
“…The region experiences much longer duration of the wet phase, with two rainy seasons each year and a longer duration of habitat inundation compared to a single rainy season in subtropical Mozambique [41] with very brief periods of inundation [42,43]. It demonstrates that Nothobranchius fishes experience variable climatic and ecological challenges that may affect their dispersal, diversification and coexistence in local killifish assemblages [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The region experiences much longer duration of the wet phase, with two rainy seasons each year and a longer duration of habitat inundation compared to a single rainy season in subtropical Mozambique [41] with very brief periods of inundation [42,43]. It demonstrates that Nothobranchius fishes experience variable climatic and ecological challenges that may affect their dispersal, diversification and coexistence in local killifish assemblages [44].…”
Section: Discussionmentioning
confidence: 99%
“…Nothobranchius populations are finely structured in small, short-existing pools in dry inland region of southern Mozambique [14,42] where main river channels form significant barriers to dispersal and lead to allopatric species and strong intra-specific diversification [15]. In contrast, humid equatorial region appears to enable greater dispersal across river channels and between river basins ( [5,10,44], present study), with Nothobranchius fishes occurring in extensive marshes and semipermanent streams [5,16,57]. Nothobranchius fishes are also present in the elevated part of equatorial East Africa (> 800 masl) and it remains to be tested how local populations are structured there.…”
Section: Discussionmentioning
confidence: 99%
“…This could promote diversification if niche divergence results in reproductive isolation among populations (Nosil 2012). Alternatively, brain morphologies in kingfishers, if linked to frequent behavioral innovations (Sol et al 2005a) or patterns that govern dispersal (Sol et al 2010), could drive rapid speciation on islands (Andersen et al 2018) through enabling clades to take advantage of ecological or "spatial" opportunity (sensu Lambert et al 2019) available in island archipelagos that causes genetic divergence between populations (Price 2008). Indeed, the two kingfisher subclades with the fastest diversification rates, Todiramphus and Ceyx (Andersen et al 2018), also have the highest rates of brain shape evolution (fig.…”
Section: Accelerated Brain Shape Evolution and Rapid Diversification Ratesmentioning
confidence: 99%
“…A study of 48 species in the comparable African annual killifish genus Nothobranchius showed that most assemblages showed little variation in body size and only a single group of coexisting species exhibited size differences that may have been the result of ecological character displacement (Lambert, Reichard, & Pincheira-Donoso, 2019). In the La Plata and Patos Lagoon areas small, similar-sized Austrolebias species co-occur ( Figure 1), along with the larger species.…”
Section: A Single Selection Regime Shift For Body Sizementioning
confidence: 99%